Hyaluronic acid-modified multiwalled carbon nanotubes for targeted delivery of doxorubicin into cancer cells. (20th March 2015) - Cao, Xueyan; Tao, Lei; Wen, Shihui; Hou, Wenxiu; Shi, Xiangyang
Graphical abstract: Highlights: Modification of PEI, FI, and HA does not appreciably change the morphology of MWCNTs. MWCNT/PEI–FI–HA/DOX complexes display a pH-responsive drug release behavior. MWCNT/PEI–FI–HA carrier is cytocompatible in the given concentration range. MWCNT/PEI–FI–HA/DOX complexes can target cancer cells via receptor-mediated manner. MWCNT/PEI–FI–HA/DOX complexes display a specific therapeutic effect to cancer cells. Abstract: Development of novel drug carriers for targeted cancer therapy with high efficiency and specificity is of paramount importance and has been one of the major topics in current nanomedicine. Here we report a general approach to using multifunctional multiwalled carbon nanotubes (MWCNTs) as a platform to encapsulate an anticancer drug doxorubicin (DOX) for targeted cancer therapy. In this approach, polyethyleneimine (PEI)-modified MWCNTs were covalently conjugated with fluorescein isothiocyanate (FI) and hyaluronic acid (HA). The formed MWCNT/PEI–FI–HA conjugates were characterized via different techniques and were used as a new carrier system to encapsulate the anticancer drug doxorubicin for targeted delivery to cancer cells overexpressing CD44 receptors. We show that the formed MWCNT/PEI–FI–HA/DOX complexes with a drug loading percentage of 72% are water soluble and stable. In vitro release studies show that the drug release rate under an acidic condition (pH 5.8, tumor cell microenvironment) is higher than that under physiological condition (pH 7.4). Cell viability assay demonstrates that the carrier material has good biocompatibility in the tested concentration range, and the MWCNT/PEI–FI–HA/DOX complexes can specifically target cancer cells overexpressing CD44 receptors and exert growth inhibition effect to the cancer cells. The developed HA-modified MWCNTs hold a great promise to be used as an efficient anticancer drug carrier for tumor-targeted chemotherapy.